Military Corps of the Kuznetsk District in the First Half of the XVIII Century: Staff, Manpower, and Occupation in the Context of Regional Administrative Processes - Bobrov, D. S. (Вестник Кемеровского государственного университета, 2022)
The article features the staff, manpower, occupation, and subordination issues in the military corps of the Kuznetsk district in the fi st half of the XVIII century. Th frontier exploration into the southern border regions of Western Siberia caused administrative transformations in the region. The research relied on management and accounting documentation from the Russian State Archive of Ancient Acts. Th author reviewed the structure of the service activities of the irregular military corps, which included both ordinary assignments to the border area for riverside patrol and extraordinary assignments for the construction of new fortifications. The Kuznetsk authorities did their best to reduce the administrative burden. The archival documents prove that the actual number of the military people in the district reduced as a result of the changes in the military, political, and management situation. By the mid 1740s, the local civil authorities had completely lost administrative control over the military staff, which passed into the hands of military departmental structures.